The role of universities in peripheral regions: the case of the North Wales and Mersey Dee area. Issue 2 (3rd July 2019) - Hinfelaar, Maria; Hildreth, Paul
ABSTRACT: The purpose of this paper is to address how universities contribute through a helix model of partnership to regional development in a peripheral but functionally connected area which finds itself outside major conurbations. In doing so, it shows how local universities may collaborate with each other and with other institutional actors, including the private sector, to gather data on how their graduates contribute to the regional economy. A case study of the North Wales Mersey Dee area (the 'NWMD'), a cross-border region within the UK, provides the evidence base. There are gaps in international studies into how universities contribute to the development of their cities and regions, because these studies typically assume that the university is part of an urban concentration with the impact of their development and engagement radiating out into the hinterland. This study explores a scenario with a more dispersed picture, requiring even more effort from key stakeholders, along with the universities, to effect positive change through a policy agenda of 'place-based' strategies. Recommendations are made for longitudinal studies in similarly peripheral and under-performing regions to gauge how universities can work within local partnerships, leveraging government-backed investment to drive improvements.